2008
DOI: 10.1002/ijc.23957
|View full text |Cite
|
Sign up to set email alerts
|

An epigenetic marker panel for screening and prognostic prediction of ovarian cancer

Abstract: Aberrant CpG island hypermethylation is a common finding of cancers, which might be detectable in the tissue or serum of affected patients. We analyzed DNA methylation by methylationspecific polymerase chain reaction of 7 genes, which included secreted frizzled receptor proteins 1, 2, 4, 5 (SFRP1, 2, 4, 5), SRYbox 1 (SOX1), paired box gene 1 (PAX1) and LIM homeobox transcription factor 1, alpha (LMX1A) in primary tumor samples from 126 patients with ovarian cancer, 75 with a benign tumor and 14 with borderline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 38 publications
4
119
0
3
Order By: Relevance
“…Accumulating evidence indicates that SFRP2, an important member of the SFRP family, functions as a negative regulator of the oncogenic Wnt pathway through competing with frizzled membrane-bound receptors [18,19]. In a broad range of malignancies including CRC, epigenetic inactivation of SFRP2 by promoter methylation is frequently detected [17,[20][21][22][23]. Here we demonstrated that SFRP2 hypermethylation mostly frequently occurred in CRC patients, followed by patients with advanced adenomas and hyperplastic polyps.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Accumulating evidence indicates that SFRP2, an important member of the SFRP family, functions as a negative regulator of the oncogenic Wnt pathway through competing with frizzled membrane-bound receptors [18,19]. In a broad range of malignancies including CRC, epigenetic inactivation of SFRP2 by promoter methylation is frequently detected [17,[20][21][22][23]. Here we demonstrated that SFRP2 hypermethylation mostly frequently occurred in CRC patients, followed by patients with advanced adenomas and hyperplastic polyps.…”
Section: Discussionmentioning
confidence: 60%
“…e unique structure of SFRPs enables them to bind and sequester Wnt molecules from their cognate frizzled receptors, thus interfering with the Wnt pathway. Loss of SFRP2 expression due to promoter methylation has been frequently observed in many tumors, including colorectal, ovarian, breast, gastric and liver cancers [17,[20][21][22][23]. Several earlier studies have demonstrated that the frequency of SFRP2 promoter methylation in fecal DNA is markedly increased in CRC patients compared with normal healthy controls [24][25], suggesting the SFRP2 hypermethylation in fecal DNA as a potential molecular biomarker of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…These unsatisfactory data indicated that it may be necessary to combine other detection methods to improve accuracy. LMX1A methylation is dysregulated in gastric, bladder, breast, ovarian and pancreatic cancer (55)(56)(57)(58). A study on various types of cancer may provide useful insights into the involvement of LMX1A methylation in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Combining the data for SFRP1, SFRP2 and SOX1 genes gave a relative risk for recurrence of 3.19 (p=0.013) in patients with at least one gene methylation, and combining the data for SFRP1, SOX1 and LMX1A gave a relative risk for cancerrelated death of 6.09 (p=0.010). The sensitivity and specificity were 73.08 and 75%, respectively, when any one of SOX1, PAX1 and SFRP1 genes showed methylation 62 . Further, a microarray analysis resulted in the identification of 112 highly discriminatory loci possessing a progression-free survival prediction accuracy of 95% in ovarian cancer patients by applying SAM and PAM analysis (Significance and prediction analysis of microarray).…”
Section: Methylated Dna Sequencesmentioning
confidence: 98%